Grundtvig belyst af en moderne anglist. The afhandlinger af professor Kamp Melone - Toldberg, Helge (Grundtvig-studier, 1948)
The reviews of Professor Kemp Malone's papers on Grundtvig (P. 98) have not been summarised, as the papers themselves are available in the Englishspeaking countries.